Harnessing sunflower stalk-based bowl for sustainable tobacco seedling and cultivation: influence on rhizosphere microbiome and carbon cycling - Shi, Xiaolong; Ge, Menglin; Hou, Suting; Han, Qing; Xu, Anning; Jiang, Chunji; Ma, Xin (Frontiers in Microbiology, 2025)
Microbes in the rhizosphere make significant contributions to nutrient cycling and plant health maintenance. Tobacco is an important commercial crop, and the methods used for seedling cultivation significantly influence the rhizosphere soil microenvironment. Compared to conventional seedling practices, the use of agricultural waste—such as sunflower straw—to fabricate biodegradable nursery containers represents an environmentally friendly alternative technology. This approach may exert specific potential effects on the structure and function of microbial communities in the tobacco rhizosphere. In this study, Yunyan-301 was used as the test material, and field experiments were carried out at two test sites (BT and HCZ). Each site included two treatments: conventional seedling cultivation (CK) and sunflower straw-based natural bowl seedling cultivation (T). While tobacco was harvested, a rhizosphere soil sample of tobacco was collected for microbial analysis. The results showed that sunflower straw-based natural bowl seedling cultivation led to a less diverse but functionally specialized microbial community. The specific alterations in the abundance of core taxa (e.g., Proteobacteria, Acidobacteria, Sphingomonas, Pseudoduganella, Luteitalea) suggest a potential ecological advantage, where the enriched community may be more efficient in utilizing sunflower straw-derived compounds and providing host-beneficial functions. Predictions of microbial community functions revealed that sunflower straw-based natural bowl seedling cultivation significantly enhanced the capacity of carbon fixation and oxidative phosphorylation, effectively improving the metabolic activity and carbon cycling ability of tobacco rhizosphere microbes. In summary, sunflower straw-based natural bowl seedling cultivation effectively alter the microenvironment of tobacco rhizosphere soil, thereby enriching functional microbial taxa and related metabolic pathways that were beneficial to soil health and tobacco growth. However, its effect was modulated by the environmental background of the test sites. In future research and actual production, further optimization of the sunflower straw-based natural bowl seedling cultivation should be conducted, and attempts should be made to assist in green and sustainable tobacco cultivation from the perspective of microbial community management.